FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN PERAWAT DALAM DOKUMENTASI PENGKAJIAN NYERI PQRST BERBASIS ELECTRONIC MEDICAL RECORD (ERM) DI RAWAT INAP DEWASA RS X BSD - Nober Ompusungu; Maria Lousiana; Fendy Yesayas (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
Pain assessment is an effort to overcome pain that is carried out in infants, children, adults and sedated with medication (pharmacology) or without drug administration (non-pharmacological) according to the level of pain felt by the patient. knowledge and motivation related to nurse compliance in PQRST pain assessment documentation based on Electronic Medical Record (EMR) at RS X BSD's adult inpatient. This type of research uses quantitative research methods, with a descriptive correlation research design and uses a cross sectional approach. Sampling using total sampling technique. Research respondents amounted to 60 people. Data analysis using Kendal Tau statistical test b. The results showed a relationship between the age factor (p-value 0.551), education factor (p-value 0.579), the tenure factor (p-value 0.001), so it can be concluded that the characteristics of nurses (education) are mostly Diploma three who are advocacy nurses. knowledge factor (p-value 0.007) that in general nurses' knowledge is quite good in conducting pain assessments, motivational factor (p-value 0.044) concluded that there are still nurses who have low motivation in conducting PQRST pain assessments according to hospital SPO because of personal constraints, namely less understand the EMR-based PQRST pain assessment, forgetfulness, space hassles and commitments, supervision of the ward head has not been routinely carried out. It is expected that RS X Hospital will provide formal training on pain assessment, form a pain assessment team and periodic audits of EMR-based PQRST pain assessment documentation